Rapid Shoot Regeneration from Thin Cell Layer Explants of an Endangered Medicinal Asclepiad Ceropegia spiralis L. (Plant Tissue Culture and Biotechnology, 2012)
The thin cell layers of nodes and internodes of Ceropegia spiralis L. were cultured on  MS  supplemented with BAP 13.32 µM/l + NAA 0.537 μM/l induced 17.34 ± 0.55 shoots showing extensive growth. Later on the organogenesis was also induced on MS containing BAP 13.32 µM/l + 2, 4-D 1.130 µM/l, whereas the medium with BAP 13.32 µM/l + 2, 4-D 4.52 µM/l has the highest callus producing ability in recalcitrants as well as in normal explants. Shoots developed were rooted best on 0.5 MS with NAA 10.74 μM/l. Optimum shoot and root multiplication was obtained within eight weeks.  In vitro plantlets were successfully weaned and transferred to soil with about 90 per cent survival rate. So far, more than 650 weanlings have been produced successfully and reintroduced into nature for their recovery.     Key words: Ceropegia spiralis, Thin cell layer explants, Recalcitrants, Regeneration   D. O. I. 10.3329/ptcb.v21i1.9564   Plant Tissue Cult. & Biotech. 21(1): 63-73, 2011 (June)